Palatal Gingival Recession Root Coverage: A Case Report - Maha A. Bahammam (Journal of King Abdulaziz University: Medical Sciences, 2023)
The treatment of palatal gingival recession is technically challenging due to difficult accessibility and the nature of the palatal mucosa. Treatment of this defect was not reported routinely in the literature and perhaps is not usually performed. However, palatal gingival recession defects might be indicated for the treatment in some cases. This case report presents a method of using a rotational connective tissue pedicle flap to correct a palatal gingival recession defect. Substantial amount of root coverage was obtained with this technique (85.7%). Therefore, whenever indicated, the rotational connective tissue pedicle flap can be used to correct palatal gingival recession defects